Demographic Features and Common Presentations of Schizophrenia - Ahammad, Julhash Uddin; Rahman, Md Habibur; Islam, Md Azizul; Rahman, M Sajjadur; Rabbani, MG (Journal of Armed Forces Medical College, Bangladesh, 2009)
Fifty cases of schizophrenia were assessed in Combined Military Hospital (CMH), Dhaka and National Institute of Mental Health (NIMH), Sher-e-Bangla Nagar, to ascertain the pattern of demographic features and symptom presentation in current national perspective. The study includes period from July 2004 to September 2005. Most of the patients belonged to the age ranging from 14 to 45 years throughout whole Bangladesh. It was found that 54% of the patients were male and 46% were female. The lowest age of onset was 14 year for both sexes and the highest age of onset was 45 year in female and 41 years in male. Among the schizophrenic patients 50% were unmarried and 50% were married and most of them belonged to lower economic class. In this study both the urban and rural percentage were equal (50%). Most of the patients were unemployed or recently disengaged from work place with a lower educational back ground. The most frequent patterns of symptom irrespective of demographic variables were persecutory ideas or delusion (76%). Analysis revealed that delusion of reference, grandiose delusions, delusion of control or possession of thought were significantly high among the male patients compared to female patients (p < 0.05), but no statistically significant difference was observed with other symptoms (p>0.05). Analysis found that no statistically significant difference was observed between urban and rural patients (p > 0.05) except visual and other hallucinations e.g. gustatory, olfactory which was significantly high among the urban patients (p < 0.05). The next frequent symptom was perceptual disturbances in the form of auditory hallucination (70%). Delusion of reference was about 70% along with delusion about control or possession of thoughts being approximately 42%. Key Words: Demographic features, Common presentations, Schizophrenia doi: 10.3329/jafmc.v5i1.2848 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.29-33